Twisted 3 planet of the twisted - Zafra, Jessica (Anvil Publishing, Inc., 1998)
Generation X icon Zafra continues her quest for world domination as she rants, complains, reminisces, and comments on anything and everything under the sun with her usual acerbic humor.